The Impact of Nurse-related Barriers on Kangaroo Mother Care Implementation in Kurdistan of Iraq - Sara Amin Mala; Sanna Hassan Abdul-Sahib (Kufa Journal for Nursing Sciences)
Background: The practice of Kangaroo Mother Care (KMC) is widely defined as a method of skin-to-skin contact that occurs between the mother and baby. This harmony and contact will reduce the mortality and morbidity among newborns and more specifically the preterm babies.